Purely elastic flow instabilities in microscale cross-slot devices - M. A. Alves (2015)
We present an experimental investigation of viscoelastic fluid flow in a cross-slot microgeometry under low Reynolds number flow conditions. By using several viscoelastic fluids, we investigate the effects of the microchannel bounding walls and the polymer solution concentration on the flow patterns. We demonstrate that for concentrated polymer solutions, the flow undergoes a bifurcation above a critical Weissenberg number (Wi) at which the flow becomes asymmetric but remains steady. The appearance of this elastic instability depends on the channel aspect ratio, defined as the ratio between the depth and the width of the channels. At high aspect ratios, when bounding wall effects are reduced, two types of elastic instabilities were observed, one in which the flow becomes asymmetric and steady, followed by a second instability at higher Wi, in which the flow becomes time-dependent. When the aspect ratio decreases, the bounding walls have a stabilizing effect, preventing the occurrence of steady asymmetric flow and postponing the transition to unsteady flow to higher Wi. For less concentrated solutions, the first elastic instability to steady asymmetric flow is absent and only the time-dependent flow instability is observed.